Research on Real-time and Dynamic Urban Traffic Information Service System - Hui Yu; Weihua Zhang (Institute of Advanced Engineering and Science, 2012)
With the acceleration of urbanization and the rapid growth of private cars, the traffic congestion is increasingly becoming a “chronic illness” for urban development. This paper describes what exactly the real-time and dynamic urban traffic information service systemis. Furthermore, the pieces of technology needed and the benefits of the system will be discussed. Finally, we conclude with issues and problems that to be resolved in order to have a fully functional system. DOI: http://dx.doi.org/10.11591/telkomnika.v10i4.871